1960
DOI: 10.1111/j.1399-6576.1960.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Ninhydrin Test—an Objective Method for Testing Local Anaesthetic Drugs

Abstract: SUMMARY An objective method for testing local anaesthetic drugs in human test subjects with the Ninhydrin print technique is described. The method is reliable in ulnar, median and finger nerve blocks. It is of more limited value in other blocks or for skin wheals, where it must be used together with the subjective neurological tests. A comparison between this method and the conventional technique used in ulnar nerve blocks was made. We feel that the Ninhydrin test is superior to the pin‐prick method in testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Skin electrical resistance also increases following traumatic damage to, and local anaesthetic block of, peripheral nerves [3] and, under these circumstances, geographically identical areas of analgesia and increased skin electrical resistance are demonstrated. The correlation between loss of sensation and loss of sweating, associated with changes in skin electrical resistance, has been confirmed for a variety of nerve injuries [4,5] using various techniques [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Skin electrical resistance also increases following traumatic damage to, and local anaesthetic block of, peripheral nerves [3] and, under these circumstances, geographically identical areas of analgesia and increased skin electrical resistance are demonstrated. The correlation between loss of sensation and loss of sweating, associated with changes in skin electrical resistance, has been confirmed for a variety of nerve injuries [4,5] using various techniques [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…No cases have been published in his work. Dhuner et al (1960) reported no neurogenous injury demonstrable by conventional neurological methods or by the ninhydrin method after 41 intraneural blocks. Also Highet (1942) believed intraneural injection of a local anesthetic to be safe.…”
Section: Technique For Avoiding Nerve Injury In Induction Of Nerve Blockmentioning
confidence: 95%
“…Intraneural versus extraneural block Highet (1942) induced the block intraneurally. Other authors who used this technique are Chase, Brandom, Macomber and Wang (1959), Dhuner, Edshage and Wilhelm (1960), Albert and Lofstrom (1961) and Moore (1961). According to Moore, nerve blocking is a measure to obtain "reversible chemical section of the nerve".…”
Section: Previous Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflex sweat secretion may be tested by means of radiant body heating to an increase in body core temperature of 1°C. Local sweat secretion is detected by application of ninhydrine or iodine starch and subsequent registration of colour change of the indicator (55).…”
Section: Tests Of Local Sympathetic Functionmentioning
confidence: 99%